Phylogeny, ultrastructure, histopathology and prevalence of Myxobolus oliveirai sp. nov., a parasite of Brycon hilarii (Characidae) in the Pantanal wetland, Brazil - Milanin, Tiago; Eiras, Jorge C; Arana, Sarah; Maia, Antônio AM; Alves, Anderson L [UNESP]; Silva, Márcia RM; Carriero, Mateus M; Ceccarelli, Paulo S; Adriano, Edson A (Instituto Oswaldo Cruz, Ministério da Saúde, 2010)
This paper presents the morphological, histological and ultrastructural characteristics of Myxobolus oliveirai sp. nov., a parasite of the gill filaments in Brycon hilarii from the Brazilian Pantanal. Out of 216 B. hilariispecimens examined (126 wild and 90 cultivated), 38.1% of wild specimens (n = 48) were infected. The parasites form elongated plasmodia primarily in the tip of gill filaments, reaching about 3 mm in length. A thorough comparison with all the Myxobolus species described from South American hosts, as well as nearly all the Myxobolus species described so far is provided. Partial sequencing of the 18S rDNA gene revealed a total of 1,527 bp. The Myxobolus species parasite of B. hilarii did not match any of the Myxozoa available in GenBank. In the phylogenetic analysis, M. oliveirai sp. nov. composed a monophyletic group with eight other species: five species of Myxobolus parasites of mugilid fishes, two parasites of pangasiid and one of centrarchid. Infection prevalence values of the parasite revealed no significant differences between wet and dry seasons or between males and females. The importance of the infection to the farming of the host species is emphasized.
Keywords: Myxozoa; Myxosporea; histology; molecular analysis; fish; piraputanga